The Effectiveness of Progressive Muscle Relaxation Therapy on Preoperative Anxiety: A Systematic Review - Anisa Rohmah Tika; Susiana Candrawati (Indonesian Journal of Global Health Research, 2025)
Preoperative anxiety is a common condition experienced by patients awaiting surgery. One non-pharmacological method to reduce this anxiety is Progressive Muscle Relaxation (PMR) therapy, which helps lower anxiety by systematically tensing and relaxing muscle groups.Objective: To evaluate the effectiveness of PMR therapy in reducing anxiety levels in preoperative patients. Method: This study used a systematic literature review with the PRISMA approach. Data were collected from Google Scholar, EBSCO, and Semantic Scholar using the keywords "Effect," "Progressive Muscle Relaxation," and "Preoperative Anxiety." A total of 1,342 articles were initially identified. Inclusion criteria included journals published between 2020 and 2024 that focused on the effects of PMR therapy on preoperative anxiety. After screening and reviewing the literature, seven relevant articles were selected and analyzed based on the inclusion criteria. Results: The reviewed studies showed that PMR therapy significantly reduced anxiety levels in preoperative patients. Patients with moderate to severe anxiety showed improvement to mild or moderate levels after the intervention. PMR also had positive effects on physiological parameters, such as reduced blood pressure and heart rate. 137 participants, pre-intervention anxiety levels were mild (8.75%), moderate (73%), and severe (18.25%). Post-intervention, 64.24% had mild anxiety and 35.76% had moderate anxiety.Conclusion: PMR therapy is effective in managing preoperative anxiety and improving physiological responses. It is recommended as a routine non-pharmacological intervention in clinical settings to support anxiety management without relying on sedatives.